Islamisation of town planning education: a review on the courses offered by the department of urban and regional planning, International Islamic University Malaysia - Ahmad Sarkawi, Azila; Abdullah, Alias; Md. Dali, Norimah (Malaysian Institute of Planners, 2016)
The Islamisation of the town planning education in Malaysia especially in the Department of Urban and Regional Planning, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia (IIUM) could successfully be materialized via the smart team-teaching approach where lecturers from the town planning Department collaborate with their counterpart in the Islamic studies Kulliyyah. This paper reports a desk study on the status of Islamic inputs in the current town planning course content. Out of 140 credit hours of town planning core courses and University required courses, it was found that 34% have already embodied Islamic-related topics whilst the remaining 66% were silent. Enhancements via compatible Islamic inputs to strengthen the existing curricula need to be done for the former while for the latter new Islamic inputs need to be incorporated. This paper reiterates that the epistemological and methodological approach combined is the way forward for sustainable education.